Outcomes of medial patellofemoral ligament reconstruction in patients with patella alta - Lúcio Flávio Biondi Pinheiro Junior; Marcos Henrique Frauendorf Cenni; Oscar Pinheiro Nicolai; Lucas Paschoal Horta Gomes; Rafael Soares Leal; Daniel Gonzales Pinto Coelho (Revista Brasileira de Ortopedia)
ABSTRACT Objective: To compare the clinical outcomes and the results of knee functional scores in patients with normal patellar height and patella alta who underwent isolated medial patellofemoral ligament reconstruction. Methods: A total of 37 knees from 33 patients with recurrent patellar dislocation who underwent isolated medial patellofemoral ligament reconstruction were included. Retrospectively, the postoperative clinical results were compared using the Kujala and Lysholm scores in the group of patients with normal patellar height and in those with patella alta. Results: The sample consisted of 37 patients; 16 knees of 14 patients in the group with normal patellar height, 21 knees of 19 patients in the group with patella alta. In the first group, the mean Kujala score was 85.8 and the mean Lysholm score was 85.6. In the second, the mean Kujala score was 78.1 and the mean Lysholm score was 79.7. No significant differences were observed between the groups in relation to the Lysholm (p = 0.296) and Kujala scores (p = 0.181). Conclusion: Isolated medial patellofemoral ligament reconstruction presented similar results in patients with normal patellar height and patella alta.